OPTIMALISASI TEMPAT PEMROSESAN AKHIR (TPA) BLONDO KECAMATAN BAWEN, KABUPATEN SEMARANG JAWA TENGAH - Teguh Kurniawan Abadi (Jurnal Teknik Lingkungan, 2012)
Blondo landfill is the place for final processing and it is existed in the Semarang Regency. Blondo landfill is located in Desa Blondo, Bawen Subdistrict with total area is about + ​​5 ha. Increased population, increased economic, and the advance of technology cause an increase population activities in areas such as housing, industry, commerce, agriculture and other sectors. It is causing increased consumption patterns of the population. The pattern of increased consumption will increase the amount of waste. Waste will cause environmental pollution if it’s not managed properly. Therefore, it is necessary for Blondo landfill to be able to accommodate an increase of waste’s amount. Follow up Blondo landfill site selection study’s activity, it required a plan for process and management of Final Disposal (TPA) by using a system of sanitary landfills. It can be obtained detailly in the design of Blondo landfill Semarang Regency.